Nexus of women’s participation in smallholder financial inclusion programs and economic efficiency: implications for poverty alleviation - Wang, Shangao; Mwalupaso, Gershom Endelani; Akter, Asma (Frontiers in Sustainable Food Systems, 2025)
Women in agriculture face significant barriers to land and resources, limiting their contributions to productivity and poverty alleviation. Despite extensive literature on women’s roles in agriculture, the effect and mechanisms of women’s participation (WP) in smallholder financial inclusion programs like Rural Savings and Credit Cooperatives (RUSACCOs) on economic efficiency (EE) in maize production remain underexplored. This study addresses this gap using data from 436 farm households in Zambia. Employing sample-selection stochastic cost frontier analysis, we find that WP in RUSACCOs significantly enhances EE. Notably, households without WP could improve cost efficiency by 21%, potentially reducing extreme poverty by 8%. Moreover, the findings identify agricultural informatization (AgI) as a compelling mediating mechanism: by empowering women and optimizing labor-land allocation, AgI amplifies the efficiency gains associated with WP. Overall, the study underscores the transformative potential of informal financial inclusion initiatives, such as RUSACCOs, that are gender-inclusive in advancing sustainable development goals (SDGs) 1 (poverty), 2 (hunger), and 5 (gender equality). Accordingly, policy implications emphasize the need for integrating smallholder financial inclusion programs with agricultural informatization support to strengthen the agricultural value chain and support broader socio-economic development goals among women farmers in rural settings.